Investigating the Role of Critical Reading Strategies in Developing Students’ Reading Comprehension - Andini Putri Rahmasari; Sunarti (English Language Education Department, Universitas Majalengka, 2024)
This study investigates the role of employing critical reading strategies on the reading comprehension development of high school students. The primary objective is to examine how critical reading strategies affect students' reading comprehension abilities in the classroom. The research utilizes a quantitative approach to assess the influence of critical reading strategies on students' reading comprehension, complemented by a descriptive analysis of the implementation of these strategies and their effects on students' reading progress. A within-subject design was employed, with participants undergoing instructional sessions on both conventional and critical reading strategies. Pre-Test, Treatment 1 involved conventional reading strategies, followed by a Post-Test. A Washout Period was implemented to minimize biases before Treatment 2, which focused on critical reading strategies. The population for this research comprised second-grade students at SMA Negeri 15 Samarinda, with a random sampling technique determining the sample. A standardized reading comprehension test served as the research instrument, and t-tests were utilized for data analysis, specifically concentrating on post-test scores. The findings revealed that critical reading strategies significantly enhanced students' reading comprehension. Specifically, the mean scores increased from 24.83 in the pre-test to 66.67 in the post-test, reflecting a marked improvement in comprehension abilities. The study provides valuable insights into the effectiveness of critical reading strategies in enhancing high school students' reading comprehension skills in the classroom.